Pelatihan Menulis Cerpen Sebagai Penguatan Program Literasi Pada Siswa Smp Kanzul Mubaarok Kota Bekasi - Sara Sahrazad; Maria Cleopatra; Harmi Ibnu Dja’far; Aster Pujaning Ati; Sigit Widiyarto (ABIDUMASY, 2021)
Writing was an ability that needs to be developed from an early age. The ability to write was still an obstacle for teachers and students. This was due to less than optimal reading interest. This activity took place from June to May 2021 . Activity aimed to produce a collection of short stories from the students of SMP Kanzul Mubarok. Activity was attended by 20 students and 3 teachers of SMP Kanzul Mubaarok Bekasi City. The result of the activity was the publication of short stories with characters made by students. The title of a collection of short stories created by students entitled: Can I stay, rays of guidance from the eastern horizon, from Jogya to Malaysia, and true friendship, Sabrina: a glimpse of a travel story. The final result was not everything, students' ability to write must be continuously honed and trained so that the ability to choose diction, grammar and imagination was strong. It could be concluded that students' writing talents and interests had different levels. In writing, students had different abilities, so that teachers must be able to accommodate these various abilities. Students were more excited when their short stories could be published, and given an ISBN